ACTUATING SYSTEMS BASED ON TWO BELLOWS - Vasile Sergiu JIŞA; Beniamin CHETRAN; Simona NOVEANU; Nour CRIŞAN (Fiabilitate şi Durabilitate)
This paper propose a thorough theoretical and experimental research on bellows actuators in order todesign and develop some actuating systems operated by two bellows actuators, with different options ofcorrugated items, the final scope being to establish a precise method of motion control. It is expected that mostrepresentative applications of actuators investigated will fit in field of mechanical engineering, robotics andbiomedical engineering.